The Importance Of Inner Beauty In Edith Wharton's The Age Of Innocence (1920): A Cultural Approach - Trisnawati, Ria; , Dr. M. Thoyibi, M.S (2016)
This research aims to analyze the value of beauty inside the women called inner beauty based on Edith Wharton's The Age of Innocence, to identify the types of beauty in a woman, to analyze the characteristics of outer and inner beauty of May and Ellen, and to reveal the reason Edith Wharton emphasizes the story on her novel about the inner beauty by means of Cultural approach. The type of this research is descriptive qualitative. The researcher gets the data from the novel includes the narration, monologue, and dialogue between each characters. The techniques of collecting the data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show: 1) the type of beauty in women reflected in The Age of Innocence novel. 2) the characteristcs of the inner and outer beauty. 3) the importance of inner beauty in women which is illustrated by Edith Wharton through her novel. Keyword: beauty, characteristic, Cultural approach, Edith Wharton, The age of innocence, type